Development of FBG humidity sensor via controlled annealing temperature of additive enhanced ZnO nanostructure coating - Riza, Muhammad Arif; Yun, Ii Go; Maier, Robert R.J.; Harun, Sulaiman Wadi; Ahmad Anas, Siti Barirah (Elsevier, 2022)
Hygroscopic materials are often explored and utilized as a sensing element in various devices for many different industries. Optical based sensors operate in conjunction with materials that are reactive to the parametric changes in the environment. Modified synthesis process allows formation of unique and novel nanostructures that can potentially be adapted as a sensor. This study focuses on characterizing hygroscopic behavior and exploring the sensing integration of additive enhanced zinc oxide coating for application in FBG as humidity sensor. ZnO-HMT was observed under a microscope within varied relative humidity levels. All samples of ZnO-HMT annealed at different temperatures showed water adsorption with water droplets of various sizes (∼50 µm). Hygroscopic characterization via technique adopted from ASTM- reveals that sample annealed with 140 °C showed best water adsorption and release. The sample annealed at 140 °C was then coated on to a uniform FBG and tested within sealed chamber with varying humidity range between 40 and 80 RH%. The optical spectrum was combined, and wavelength shifts has been analyzed. The sensitivity of the FBG sensor achieved up to 0.0008 nm/% within range of 40 – 80 % humidity with > 87 % linearity. The development of the low temperature modified ZnO nanostructure coated on the FBG as a humidity sensor was successful. The nanostructure can have potential impact in pharmaceutical and power storage industries due to its simplicity in synthesis which brings about lower manufacturing costs of materials for optical sensors.